The thought collective: Challenges in balancing social and financial goals (B) - Kenneth T. GOH, (Institutional Knowledge at Singapore Management University, 2019)
Case A is set in 2008. Tong Yee is a co-founder of The Thought Collective (TTC), a group of social enterprises that aimed to enhance the social capital of local society. His background in education led him to provide private lessons to underprivileged children. In 2006, he worked with his partners to launch School Of Thought (SOT), a tuition centre that focused on public welfare and charged affordable fees with the goal of maximising social impact instead of profits. TTC subsequently branched into the restaurant business in 2007 with Food For Thought (FFT) when the opportunity fortuitously arose. FFT began by donating 10% of its profits to the community. Later on, in collaboration with the National Heritage Board (NHB), a statutory board charged with preserving the shared heritage of Singapore’s diverse communities, FFT would also be a place where people gathered to share stories of their local life experiences. FFT hence aimed to provide good food for a good cause. At the end of the year, Tong and his team had to decide if a much larger restaurant location at the Singapore Botanic Gardens was worth bidding for. The area was popular with tourists and locals alike and fit their goal of bringing people together in community areas. A dynamic rental model would also allow their rent to fluctuate with sales. However, the costs would be a lot higher than at their other outlets and demand was uncertain. Case B continues in 2011. After FFT decided to rent the space at the Singapore Botanic Gardens, they suffered huge financial losses in the first few years. The team started to face new operational and staffing issues and had to figure out how to move forward or cease operations. The case also explores what the team could have done differently. Learning objectives for the students are to understand the relationship between social and financial goals; appreciate the difficulty in scaling a social enterprise; and be able to avoid decision-making biases.